(untitled) (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2016)
The aim of the paper is to compare the employers’ and employees’ insights on human capital quality defining and human capital development at organisational level, based on a survey carried out in the county of Satu Mare, Romania. Our findings show that as human capital buyers, employers understand by human capital quality professional background and skills, professional behaviour and efficiency and productivity for the organisation. As human capital sellers, for employees human capital quality means health and the ability to learn and to be suitable to the job requirements. Regarding the opportunities to develop the organisational human capital, the views of employers and employees are very different when the level of discussion is international (macro-level). Employees consider that the international environment has a greater impact on human capital development in their organisation as the employers.